Ubenimex enhances Brd4 inhibition by suppressing HEXIM1 autophagic degradation and suppressing the Akt pathway in glioma cells - Han, Liping (Oncotarget, 2017)
Inhibition of Brd4 by JQ1 treatment showed potential in the treatment of glioma, however, some cases showed low sensitivity of JQ1. In addition, the pre-clinical analysis showed its limitation by demonstrating that transient treatment with JQ1 leads to aggressive tumor development. Thus, an improved understanding of the mechanisms underlying JQ1 is urgently required to design strategies to improve its efficiency, as well as overcome its limitation. HEXIM1 has been confirmed to have an important role in regulating JQ1 sensitivity. In our study, ubenimex, a classical anti-cancer drug showed potential in regulating the JQ1 sensitivity of glioma cells using the WST-1 proliferation assay. Further studies demonstrated that ubenimex inhibited autophagy and downregulated the autophagic degradation of HEXIM1. The role of HEXIM1 in regulating JQ1 sensitivity was verified by the HEXIM1 knockdown. Since ubenimex was verified as an Akt inhibitor, we further studied the role of Akt inhibition in regulating JQ1 sensitivity and migration of glioma cells. Data showed that ubenimex improved the efficiency of JQ1 treatment and suppressed migration both in the in vitro and in vivo xenografts models. The Akt agonist attenuated these effects, pointing to the role of Akt inhibition in JQ1 sensitivity and suppressed migration. Our findings suggest the potential of ubenimex adjuvant treatment to enhance JQ1 efficiency and attenuate parts of its side effect (enhancing tumor aggressive) by regulating the autophagic degradation of HEXIM1 and Akt inhibition.